Synaptic targeting and localization of discs-large is a stepwise process controlled by different domains of the protein. - Thomas, U.; Ebitsch, S.; Gorczyca, M.; Koh, Y.H.; Hough, C.D.; Woods, D.; Gundelfinger, E.D.; Budnik, V. (Current Biology, 2000)
Membrane-associated guanylate kinases (MAGUKs) assemble ion channels, cell-adhesion molecules and components of second messenger cascades into synapses, and are therefore potentially important for co-ordinating synaptic strength and structure. Here, we have examined the targeting of the Drosophila MAGUK Discs-large (DLG) to larval neuromuscular junctions.During development, DLG was first found associated with the muscle subcortical compartment and plasma membrane, and later was recruited to the postsynaptic membrane. Using a transgenic approach, we studied how mutations in various domains of the DLGprotein affect DLG targeting. Deletion of the HOOK region-the region between the Src homology 3 (SH3) domain and the guanylate-kinase-like (GUK) domain-prevented association of DLG with the subcortical network and rendered the protein largely diffuse. Loss of the first two PDZ domains led to the formation of large clusters throughout the plasma membrane, with scant targeting to the neuromuscular junction. Proper trafficking of DLG missing the GUK domain depended on the presence of endogenous DLG.Postsynaptic targeting of DLG requires a HOOK-dependent association with extrasynaptic compartments, and interactions mediated by the first two PDZ domains. The GUK domain routes DLG between compartments, possibly by interacting with recently identified cytoskeletal-binding partners.